2014
DOI: 10.1210/en.2014-1112
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diet-Induced Obesity on Intestinal Stem Cells: Hyperproliferation but Impaired Intrinsic Function That Requires Insulin/IGF1

Abstract: Nutrient intake regulates intestinal epithelial mass and crypt proliferation. Recent findings in model organisms and rodents indicate nutrient restriction impacts intestinal stem cells (ISC). Little is known about the impact of diet-induced obesity (DIO), a model of excess nutrient intake on ISC. We used a Sox9-EGFP reporter mouse to test the hypothesis that an adaptive response to DIO or associated hyperinsulinemia involves expansion and hyperproliferation of ISC. The Sox9-EGFP reporter mouse allows study and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 43 publications
7
94
2
Order By: Relevance
“…[9,13,14,5759] Recent studies in murine models have demonstrated that prolonged high-fat load can increase the proportion of intestinal stem cells (ISCs), augment stem cell self-renewal, and provide non-ISCs (differentiated intestinal cells) with stemness attributes through activation of PPARD signaling, all of which may contribute to tumor development. [14,15] Additional studies have shown that the number of ISCs may be reduced by fasting and increased by refeeding.…”
Section: Discussionmentioning
confidence: 99%
“…[9,13,14,5759] Recent studies in murine models have demonstrated that prolonged high-fat load can increase the proportion of intestinal stem cells (ISCs), augment stem cell self-renewal, and provide non-ISCs (differentiated intestinal cells) with stemness attributes through activation of PPARD signaling, all of which may contribute to tumor development. [14,15] Additional studies have shown that the number of ISCs may be reduced by fasting and increased by refeeding.…”
Section: Discussionmentioning
confidence: 99%
“…These data support the idea that the kcal amount of food alters intestinal epithelial proliferation and that there can be lasting effects of the amount of food eaten on the proliferative capacity of the intestinal epithelium. 8,37,38 Compensatory mechanisms occur after ANS denervation in order to reestablish intestinal function under a variety of conditions and include (1) an upregulation of gastrointestinal (GI) receptor expression, (2) compensation by the nondenervated ANS branch and (3) enteric nervous system modulation. For example, PNS denervation initially decreases intestinal motility, 39 a process which is heavily mediated by serotonin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a long-term (more than six months) HFD expands ISC numbers and reduces the numbers of their niche Paneth cells (Fig. 1) [4447]. In addition to these quantitative changes, ISCs, identified by the Lgr5-eGFP high reporter, and non-stem cell progenitors (Lgr5-eGFP low ) undergo qualitative changes: 1) ISCs acquire niche independence—no longer requiring Paneth cells to initiate ex vivo organoids, and 2) non-stem cell progenitors obtain features of stemness—acquiring the potential to form ex vivo organoids [46••].…”
Section: High Fat Dietmentioning
confidence: 99%